Pendampingan Penguatan Branding dan Digital Marketing pada Desa Wisata Lembah Winden Wonosalam - Arviani, Heidy; Yudha, Dhian Satria; Atasa, Dita; Yulianto, Teguh (Jurnal Gema Ngabdi, 2024)
The tourism sector has great potential in driving economic growth, including through the development of tourism villages. However, challenges such as duplication of models, lack of standardization, and low maintenance of infrastructure often hinder optimization. Winden Valley Tourism Village in Wonosalam, Jombang, has attractive natural tourism potential but has not been maximized. To overcome these obstacles, assistance was provided that focused on branding and digital marketing strategies. The assistance includes the utilization of social media, website development, and the use of mobile cashier applications to improve service efficiency. The methods used include proposal preparation, observation, brainstorming, and evaluation through pre-test and post-test. The results of the mentoring showed a significant increase in the knowledge and skills of business actors. The initial pre-test score of 60 increased to 105 in the post-test. With the right branding strategy and digital technology support, Winden Valley Tourism Village is expected to increase its visibility as a tourist destination and encourage local economic growth.